2022
DOI: 10.1007/s11842-022-09511-1
|View full text |Cite
|
Sign up to set email alerts
|

How financially viable is smallholder forestry? A case study with a high-value tropical forestry species

Abstract: This paper evaluates the financial performance and risk of high-value tropical forestry under the challenges faced by smallholders, using Vanuatu sandalwood as a case study. We developed a financial model to predict returns from smallholder-based sandalwood plantations. The model was used to investigate the following issues typically faced by smallholders: (i) what is the financial impact of smallholders harvesting trees at young ages because of fear of theft or cyclone damage? (ii) how does the opportunity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, they can maintain their comparative advantage by supplying niche markets with a diverse product assortment (Scherr 2004). A potential business model could involve timber cultivation for a specific market segment, such as high-value sawlogs for furniture production or woodchips (Tham et al 2021, Ota et al 2022). Additionally, households can diversify their income through the cultivation, value-added processing, and commercialisation of high-value non-timber forest products (Meinhold and Darr 2019).…”
Section: Methodsmentioning
confidence: 99%
“…However, they can maintain their comparative advantage by supplying niche markets with a diverse product assortment (Scherr 2004). A potential business model could involve timber cultivation for a specific market segment, such as high-value sawlogs for furniture production or woodchips (Tham et al 2021, Ota et al 2022). Additionally, households can diversify their income through the cultivation, value-added processing, and commercialisation of high-value non-timber forest products (Meinhold and Darr 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Growing sandalwood is a long‐term investment as it takes approximately 25 years for trees to mature and reach optimal levels of oil production. However, sandalwood is commonly harvested as young as 15 years (Bush et al, 2020) and identifying opportunities for early return on plantation investments is being explored as a priority to encourage smallholders to delay harvest (Ota et al, 2022). Expected production of sandalwood in 2040 indicates that India is positioned to be the largest producer globally, followed by Australia and Indonesia, with substantial growth in production in the Pacific and South East Asian regions (Table 1 and Figure 1; Thomson, 2020).…”
Section: Status Of Sandalwood Supplymentioning
confidence: 99%
“…Despite overwhelming interest in sandalwood farming globally, the length of time it takes for trees to mature inevitably delays return on investment, and it is expensive to protect trees while they reach maturity (Ota et al, 2022; Viswanath et al, 2020). Methods have been developed to assist with mitigating the risk of sandalwood theft such as vibration sensing alarms that are attached to trees and send and alert to forestry staff when the vibrations from tree‐cutting are detected (Hamza et al, 2013; Kumar et al, 2020).…”
Section: Status Of Sandalwood Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these plantation resources are beginning to mature and can satisfy international demand for sustainably sourced sandalwood products. Financially viable sandalwood production has already been demonstrated in smallholder agroforestry systems for places like Fiji (Harrison & Harrison, 2016), Vanuatu (Page et al, 2010;Ota et al, 2022) and India (Divakara et al, 2018). Recent research in Timor-Leste has also demonstrated the potential for profitable sandalwood production in smallholder systems (Page et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%